Implied volatility sentiment: A tale of two tails - Luiz Felix; Roman Kräussl; Philip Stork (Goethe University Frankfurt, Center for Financial Studies (CFS), 2017)
Low probability events are overweighted in the pricing of out-of-the-money index puts and single stock calls. We find that this behavioral bias is strongly time-varying, linked to equity market sentiment, and higher moments of the risk-neutral density. An implied volatility (IV) sentiment measure that is jointly derived from index and single stock options explains investors' overweight of tail events the best. Our findings also suggest that IV-sentiment predicts equity markets reversals better than overweight of small probabilities itself. When employed in a trading strategy, IV-sentiment delivers economically significant results, which are more consistent than the ones produced by the market sentiment factor. The joint use of information from the single stock and index option markets seems to explain the forecasting power of IVsentiment. Out-of-sample tests on reversal prediction show that our IV-sentiment measure adds value over and above traditional factors in the equity risk premium literature, especially as an equity-buying signal. This reversals prediction seems to improve time-series and cross-sectional momentum strategies.
Keywords: G12; G14; G17; 330; sentiment; implied volatility skew; equity-risk premium; reversals; predictability